Content validity-based evaluation criteria system for siting wind-solar plants - Sachit, Mourtadha Sarhan; Mohd Shafri, Helmi Zulhaidi; Abdullah, Ahmad Fikri; Mohd Rafie, Azmin Shakrine; Hanoon, Sadeq Khaleefah (Baghdad University, 2024)
The spatial assessment criteria system for hybridizing renewable energy sources, such as hybrid solar-wind farms, is critical in selecting ideal installation sites that maximize benefits, reduce costs, protect the environment, and serve the community. However, a systematic approach to designing indicator systems is rarely used in relevant site selection studies. Therefore, the current paper attempts to present an inclusive framework based on content validity to create an effective criteria system for siting wind-solar plants. To this end, the criteria considered in the related literature are captured, and the top 10 frequent indicators are identified. The Delphi technique is used to subject commonly used factors to expert judgments. Other factors are considered according to expert recommendations. In this context, the assessment tool was a combination of questionnaires and interviews with experts from scientific backgrounds that reflect the measurement target. The item-level content validity index (I-CVI) is applied along with the modified Kappa statistic (k*) to analyze expert ratings and suggestions. The results demonstrate the superiority of 9 and 4 commonly used factors and the suggested factors, respectively. The 13 criteria have achieved high agreement among experts at I-CVIs ≥ 0.78 and k*s > 0.76. The conclusion can be drawn that the modified Kappa statistic used in this analysis has a more significant effect on eliminating irrelevant factors. The current methodology and consequences might pave the way for making informed decisions to locate wind and solar farms.